2014
DOI: 10.1186/s13054-014-0475-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of patients infected with HIV in the intensive care unit (2005 through 2010): significant role of chronic hepatitis C and severe sepsis

Abstract: IntroductionThe combination antiretroviral therapy (cART) has led to decreased opportunistic infections and hospital admissions in human immunodeficiency virus (HIV)-infected patients, but the intensive care unit (ICU) admission rate remains constant (or even increased in some instances) during the cART era. Hepatitis C virus (HCV) infection is associated with an increased risk for hospital admission and/or mortality (particularly those related to severe liver disease) compared with the general population. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
4
14
3
2
Order By: Relevance
“…Although univariate analysis identified mean age, primary diagnostic category, sepsis acquired during the ICU stay, inotrope/vasopressor administration, mechanical ventilation, haemodialysis, median CD4 cell count, median APACHE II score, median SOFA score and median length of ICU stay as significant factors associated with ICU mortality, only a non‐sepsis diagnosis, inotrope/vasopressor administration and mechanical ventilation were major contributors to ICU mortality in the multivariate analysis. These findings are similar to those of other studies which also evaluated significant contributors to ICU survival/mortality .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although univariate analysis identified mean age, primary diagnostic category, sepsis acquired during the ICU stay, inotrope/vasopressor administration, mechanical ventilation, haemodialysis, median CD4 cell count, median APACHE II score, median SOFA score and median length of ICU stay as significant factors associated with ICU mortality, only a non‐sepsis diagnosis, inotrope/vasopressor administration and mechanical ventilation were major contributors to ICU mortality in the multivariate analysis. These findings are similar to those of other studies which also evaluated significant contributors to ICU survival/mortality .…”
Section: Discussionsupporting
confidence: 91%
“…These included poor baseline health, higher severity of acute illness and delayed delivery of critical care . In addition, a higher severity of illness score, low serum albumin, requirement for vasopressor or inotropic support, need for mechanical ventilation, Pneumocystis carinii pneumonia (PCP) diagnosis and the presence of other AIDS‐related illnesses have also been associated with poorer outcomes in patients with HIV infection . Surprisingly, the CD4 cell count and HIV viral load were not shown to predict ICU survival .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previously published data, our patient population was young (mean age 44 years) [5, 12, 19]. Nearly half of patients were aboriginal and the prevalence of substance use and HCV coinfection were high.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the immunosuppressive effect of HCV could explain our results. Previous studies assessing the role of HCV as an immunomodulator reported a higher number of infectious complications in liver transplant recipients with HCV infection . Moreover, viral infections caused by CMV, BK virus, or HCV can produce allograft injury through production of proinflammatory cytokines (eg, IL‐1, IL‐6, IL‐8, and tumor necrosis factor alpha) and profibrotic and vasculopathic growth factors (eg, TGF‐beta and platelet‐derived growth factor), which induce proliferation of fibroblasts with a direct effect on the development of chronic allograft dysfunction .…”
Section: Discussionmentioning
confidence: 99%